Beating Drug Tests and Defending Positive Results A Toxicologist$1 (Bs Perspective /s - Dasgupta, Amitava; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
A majority of the Fortune 500 Companies implement some practice of workplace drug testing in their company policies. This practice was first initiated by President Ronald Reagan when he ordered federal agencies to drug test federal employees involved in sensitive positions as well as positions involving public safety. As a practicing toxicologist, Dr. Amitava Dasgupta is involved with the pre-employment drug testing at his own hospital and aptly shares his expertise in Beating Drug Tests and Defending Positive Results: A Toxicologist$1 (Bs Perspective, which covers all major issues concerning how people try to beat drug tests and defend positive test results. In each chapter, extensive references are cited so that readers can access more information on a particular topic that may interest them. The book will undoubtedly prove helpful to toxicologists, medical technologists, pathologists, human resources professionals and anyone interested in workplace drug testing.s
Beating Drug Tests and Defending Positive Results: A General Overview -- Pharmacology of Commonly Abused Drugs -- Workplace Drug Testing: SAMHSA and Non-SAMHSA Drugs -- Synthetic Urine, Flushing, Detoxifying, and Related Agents for Beating Urine Drug Tests: Are They Effective? -- Household Chemicals and Internet Based Products for Beating Urine Drug Tests -- Adulterating Hair, Oral Fluid, and Sweat Specimens for Drug Testing -- Defending Positive Opiate and Marijuana Test Results -- Defending Positive Cocaine Tests -- Defending Positive Amphetamine Results -- Analytical True Positives in Workplace Drugs Testings Due to Use of Prescription and OTC Medications.
Keywords: Medicine; Toxicology; Forensic medicine; Forensic Medicine; Biomedicine; Forensic Science; Forensic Medicine; Pharmacology/Toxicology.